Towards a national ecosystem to create scientists and sovereign knowledge - Al-Saud, Bandar Abdullah; Al-Abduljabbar, Abdulhamid Abdurahman (Arab Journal for Sciences and Research Publishing, 2023)
This paper presents a vision and basis for establishing a sustainable national ecosystem to support creation of scientists and sovereign knowledge in order to create a sustainable environment for social and economic development and prosperity, and introduce necessary foundations and tools. It begins with a summary on knowledge and science creation throughout human history, followed by a review of three important types of science enabling organizations internationally; these are: advanced studies institutes, science academies, and science museums. The case is made for establishing a national and central body to set strategy and targets, lead the formation and execution of the ecosystem, by enabling stakeholders concerned with science, innovation and scientific research, to exercise and implement partnerships through utilizing available tools and capabilities. Two important outputs from applying this ecosystem are identified. The first is producing a necessary critical mass of scientists, which is nurtured by a wide popular scientific culture spread among the population stemming from genuine passion and reverence for science. The second output is producing original scientific knowledge, which contributes to new scientific findings and theories, and enhances national knowledge content and the capacity of vital sectors within society, in order to achieve faster response to sustainable development requirements. The paper concludes with proposing indicators to measure the maturity and success of the ecosystem in producing the intended knowledge content through innovative scientists driven by science to achieve sustainable civilization and to strengthen national development and sovereignty.
Keywords: Sovereign Knowledge; Science; Education; Making of Scientists; Sustainable Development; Eco-system